Sensorless Speed Control of Asynchronous Motor Using Sliding Mode Observer - Nguyen, Huy Phuong (Old Journal, 2019)
The application of speed observer instead of direct speed sensor helps asynchronous motor drive reduce cost and improve reliability. The information required for rotor speed estimation is extracted from measured stator voltages and currents at the motor terminals. Different speed estimation algorithms are used for this purpose. The paper concentrates on the design of sliding mode observer for estimating rotor speed in asynchronous motor drive. After general introduction of field-oriented control method for asynchronous motor using voltage source inverter without speed sensor, the paper concentrates on a calculating method of rotor speed using Sliding Mode Observer. In order to confirm the proposed estimation method, an experimental setup of asynchronous motor drive has been built. The experiment results show that the asynchronous motor drive with sensorless field-oriented control strategy works stably in all conditions.